A hybrid DWT-DCT-SVD watermarking scheme using arnold transform - Huynh, Van-Thanh; Nguyen, Thai-Son; Vo, Thanh-C (Institute of Advanced Engineering and Science, 2025)
In telemedicine, medical images and electronic patient records (EPRs) are frequently transmitted and stored, making them vulnerable to tampering and theft. To ensure data security and copyright protection, this paper proposes a hybrid watermarking scheme based on discrete wavelet transform (DWT), discrete cosine transform (DCT), and singular value decomposition (SVD). The method uses a two-level DWT to decompose the image, applies DCT to selected sub-bands, and embeds two watermarks. The first is a logo used for ownership verification, and the second is an EPR encrypted with the Arnold transform for privacy protection. SVD is then used to enhance robustness. Experimental results show that the proposed scheme achieves better image quality and stronger resistance to common attacks compared with existing watermarking methods.